2013
DOI: 10.1247/csf.13012
|View full text |Cite
|
Sign up to set email alerts
|

The Antipsychotic Olanzapine Induces Apoptosis in Insulin-secreting Pancreatic β Cells by Blocking PERK-mediated Translational Attenuation

Abstract: ABSTRACT. Patients with schizophrenia receive medication to alleviate various symptoms, but some efficacious second generation antipsychotics, particularly olanzapine, can cause obesity, dyslipidemia, and diabetes mellitus. It has been generally considered that olanzapine contributes to the development of diabetes by inducing obesity and subsequent insulin resistance. In this study, we examined the effect of olanzapine and risperidone, another second generation antipsychotic, on a hamster pancreatic β cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Another study showed that olanzapine induced ER stress and reduced insulin secretion in hamster pancreatic β cells (Ozasa et al. 2013). However, the pathophysiological significance of this effect remains unclear since this drug classically induces hyperinsulinemia, even in the absence of weight gain (Melkersson and Dahl 2003; Teff et al.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that olanzapine induced ER stress and reduced insulin secretion in hamster pancreatic β cells (Ozasa et al. 2013). However, the pathophysiological significance of this effect remains unclear since this drug classically induces hyperinsulinemia, even in the absence of weight gain (Melkersson and Dahl 2003; Teff et al.…”
Section: Introductionmentioning
confidence: 99%
“…Olanzapine has the highest binding affinity with the M3 receptor of all the SGAs [10] and also alters M3 receptor density in discrete 32 nuclei of the hypothalamus and caudal brainstem regions that regulate glucose homeostasis and insulin secretion through vagal innervation of the pancreas [11]. Recently, Ozasa et al [12] showed that olanzapine but not risperidone evoked mild endoplasmic reticulum (ER) stress, as evidenced by mild activation of the ER stress sensor molecule PKR-like ER kinase (PERK) on a hamster pancreatic β cell line. However, phosphorylation of the α subunit of eukaryotic initiation factor 2 (elF2α), an event immediately downstream of PERK activation [13], was not observed in cells treated with olanzapine.…”
Section: Discussionmentioning
confidence: 99%
“…Antipsychotic structural differences may be key to the effect on eIF2α [13]. It is speculated that the chemical structure of olanzapine interferes with recruitment of eIF2α by interacting with PERK's large kinase insert loop, which is particularly important when PERK is only mildly activated [12]. In conclusion, olanzapine seems to directly impair pancreatic beta cell function.…”
mentioning
confidence: 99%
“…However, phosphorylation of eIF2α was not observed in cells treated with olanzapine. Thus, protein synthesis continued despite PERK activation, and ER stress was sustained, which resulted in marked apoptosis of beta cells by olanzapine [12]. Antipsychotic structural differences may be key to the effect on eIF2α [13].…”
mentioning
confidence: 99%